Metodología para el diseño y construcción de bombas centrífugas radiales hasta 1.5 HP de potencia utilizando tecnología local. - Tapia Solano, Javier Francisco (2014)
In the present research Project the different stages are detailed in which the methodology was developed to the design and implementation of a prototype of centrifugal pump of radial flow applying local technology and using the range of tools of the mechanic shop of the Area of Energy Industries and Non-Renewable Natural Resources of the National University of Loja. The first stage consists in to determine the requirements that are necessary to the implementation of the prototype, determining the hydraulic parameters and mechanical of the impeller or redote and the diffuser box of the implement prototype, after that the construction process is implemented and it is determined with the use of this methodology, the steps, the techniques that will used to the construction of the principal parts of the project, resorting to the machining by CNC in which the mechanism is highlighted of the driving, housing and construction of the cotter, using the milling machine CNC (computerized numerical control), subsequently the tests of operation of the centrifugal pump, and the construction of the characteristics curves. Followed by the conclusions and recommendations are the result of all this experience and will certainly not the basis for any similar type of research raises.